Pelatihan Dan Bimbingan Teknis Penataan Sirkulasi Drainase, Tata Rumah Sehat & Penataan Jalan di Lingkungan IX RT/RW IV Kel. Bantan, Medan - Kamaluddin Lubis; Ninny Asnidar Siregar; Nuril Mahda Rangkuti; Nela Permata Sari Lubis (Pelita Masyarakat, 2022)
The arrangement of buildings and the environment is needed as an effort to control the use of space, especially to realize the built environment, both in urban and rural areas, especially the physical form of buildings and their environment. The vision of structuring buildings and the environment is the realization of buildings and environments that are livable and have identity, while the missions are: (1) Empowering the community in the administration of buildings that are orderly, livable, self-identified, harmonious and harmonious, (2) Empowering the community so that independent in structuring a productive and sustainable environment. The physical health of the house is also closely related to 1) the availability of clean/drinking water that meets the requirements and quality of clean/drinking water; 2) availability of a wastewater treatment system that does not pollute clean water sources; 3) the availability of a waste disposal system (starting from storage & sorting, disposal and composting); 4) the availability of a rainwater drainage system so that it does not inundate the home environment. optimal health status, and the house meets the requirements of a healthy house such as ventilation, adequate lighting, buildings according to the number of occupants of the house and supported by the health of the surrounding environment. A house or housing is said to be habitable if it meets the minimum requirements regarding safety, health, comfort, and convenience (4K) for its occupants.